Effects of Ca2+ on migration of dissolved organic matter in limestone soils of the southwest China karst area. (4th October 2021) - Xiao, Peiwen; Xiao, Baohua; Adnan, Muhammad
Abstract: The prospect of carbon sequestration in soils of karst areas remains unclear. The study on migration and transformation of dissolved organic matter (DOM) in limestone soil under the high calcium environment of karst regions has seldom been reported. This study conducted soil column experiments on two surface soils (H1 and S2) and two subsurface soils (H2 and S2) from two limestone soil profiles in the karst region of southwest China and investigated their DOM leaching behaviours under different Ca 2+ concentration levels. The results showed that the DOM leaching process can be described by the Elovich equation, including a rapid DOM release stage and the relatively stable DOM release stage. When the Ca 2+ concentration of eluent increases from 0 to 2.5 mmol L −1, the percentage of dissolved organic carbon (DOC) loss in H1, H2, S1, and S2 soils decreased from 66.3% to 58.8%, from 76.2% to 72.4%, from 73.0% to 68.8%, and from 52.5% to 46.6%, respectively, and the apparent molecular weight of leached DOM increases, the aromaticity of leach DOM and the contribution of humic‐like components decrease. The results further show that the influence of Ca 2+ on easily leaching DOM is stronger than that on the stable DOM, indicating that high Ca 2+ runoff can enrich high aromaticity and high molecular weight soil organic matter (SOM) in the limestone soil during the leaching process. This research is helpful to understand the migration and fate of SOM in limestone soils and provides theoretical support for increasing soil carbon sinks in karst areas.